Study on crack alleviation in bending of AL-2024 for wing ribs fabrication [electronic resource] - Firdaus Che Ahmad, 1987- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2010